2023
DOI: 10.1186/s12916-023-02739-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating amino acid levels and colorectal cancer risk in the European Prospective Investigation into Cancer and Nutrition and UK Biobank cohorts

Abstract: Background Amino acid metabolism is dysregulated in colorectal cancer patients; however, it is not clear whether pre-diagnostic levels of amino acids are associated with subsequent risk of colorectal cancer. We investigated circulating levels of amino acids in relation to colorectal cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) and UK Biobank cohorts. Methods Concentrations of 13-21 amino acids were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
(83 reference statements)
2
11
0
Order By: Relevance
“…Some amino acids play an important role in tumorigenesis. Dietary methionine supplementation activates T cells and suppresses tumor progression in immunocompetent mice [ 20 ]; the serum level of lysine is inversely associated with colorectal cancer risk in the European Prospective Investigation into Cancer and Nutrition and UK Biobank cohorts [ 21 ]. The recovery of the amino acid pathways affected by AOM/DSS may also be a potential strategy for the treatment of CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Some amino acids play an important role in tumorigenesis. Dietary methionine supplementation activates T cells and suppresses tumor progression in immunocompetent mice [ 20 ]; the serum level of lysine is inversely associated with colorectal cancer risk in the European Prospective Investigation into Cancer and Nutrition and UK Biobank cohorts [ 21 ]. The recovery of the amino acid pathways affected by AOM/DSS may also be a potential strategy for the treatment of CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated the ability of metabolomics to identify metabolic pathway alterations associated with CRC 11 , 29 37 . These include TCA cycle-related metabolites reflecting impaired mitochondrial respiration and oxidative stress 10 , 11 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence suggests that some circulating metabolites are causally related to cancer development. Lipids and amino acids were the most abundant circulating metabolites associated with CRC risk 5,[8][9][10] . Elevated levels of triglycerides, phospholipids, and cholesterol may promote cancer cell growth and proliferation by serving as an energy source and inhibiting CD8 + T cell proliferation 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids function as building blocks of proteins, precursors of various signaling molecules, and energy sources. Levels of certain amino acids, such as Alanine and Histidine, have been shown to inversely associate with the cancer stage 12 . In addition, Histidine concentration in blood was shown to be inversely associated with CRC risk 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation